1987
DOI: 10.5636/jgg.39.377
|View full text |Cite
|
Sign up to set email alerts
|

Observations of solar wind ions by the interplanetary spacecraft Suisei (PLANET-A).

Abstract: Overview of the solar wind ion measurements which were carried out by the Japanese interplanetary spacecraft Suisei (PLANET-A) is presented. The instrumentation and results obtained from the initial two-month observations are described.(1) The experiment has been successful in resolving solar wind ions into H+, He++, and, sometimes, other minor constituents, such as 0+6, Si+' , Si+8, and iron groups. These heavy ions, which are considered to contain information on the solar corona, have been identified clearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The plasma instrument (ESP instrument: _Energy Spectrum of_Particles) on Suisei [Mukai and Miyake, 1986;Mukai et al, 1986a] was operated in the two-dimensional mode during the encounter with comet Halley. The geometric factor ((SfiAE)/E) is 2.3 x 10 -4cm 2 sr and the field of view is 5øx 60 ø, with the longer dimension being perpendicular to the ecliptic plane.…”
Section: Instrumentationsupporting
confidence: 81%
“…The plasma instrument (ESP instrument: _Energy Spectrum of_Particles) on Suisei [Mukai and Miyake, 1986;Mukai et al, 1986a] was operated in the two-dimensional mode during the encounter with comet Halley. The geometric factor ((SfiAE)/E) is 2.3 x 10 -4cm 2 sr and the field of view is 5øx 60 ø, with the longer dimension being perpendicular to the ecliptic plane.…”
Section: Instrumentationsupporting
confidence: 81%
“…The measurement principle and method of LEP-SW are quite similar to those of LEP-EA-i, however LEP-SW uses a 270°-spherical electrostatic analyzer with the field of view of 5° x 60°. Figure 6 shows schematically the principle of the 270°-spherical analyzer, which has been proved to be very useful for the solar wind measurement onboard PLANET-A (Suisei) spacecraft (Mukai et al, 1987). skewing, compared to those of the EA-i sensor shown in Fig.…”
Section: Lep-swmentioning
confidence: 99%
“…It has been reported that the mass range of ions in the solar wind is distributed from 1 for H to 136 for Xe (Bame, 1972;Zurbuchen, 1998;Growther et al, 2012), with energy levels ranging mainly from 300 eV to 4 keV exibiting a peak at 1 keV in terms of protons, velocities ranging from 280 km/s to 870 km/s (Bame, 1972;Zastenker & Borodkova, 1991), angular dispersion of flying direction ranging by +/-10 degrees (Hundhausen et al, 1967;Mukai et al, 1987), ion flux ranging from 3x10 8 to 3.8x10 8 ion/cm 2 /s at 1 AU (Ryden, 2011;Zastenker & Borodkova,1991), and charge states distributed from +1 to +14 (Bame, 1972;Ipavich, 1997). To analyze the solar wind, it is necessary to shape an ion beam by separating the dispersed excess part of the solar wind, selecting the specified energy ions, and maintaining a sufficiently fine beam diameter on the image sensor.…”
Section: Solar Wind Analysis Utilizing Ref Unit(s)mentioning
confidence: 99%
“…Many attempts to elucidate solar wind dynamics have been carried out over six decades, accumulating data and experience to update our knowledge (Asbridge et al, 1976;Bame, 1972;Bame et al, 1968;Feldman et al, 1976;Kallenbach et al, 1997;Marsch, E., 2006;Neugebauer, M., 2002;Parker, 1961;von Steiger et al, 1995). Numerous in-situ instruments to analyze charged particles in the solar wind have been placed into space, and they have been sending large volumes of data including energy, velocity, abundance ratio, isotopic ratio, and charge state distribution statistics (Bame et al, 1968;Bochsler et al, 1996;Crowther et al, 2012;Geiss, 1972;Gloeckler et al, 1995;Hundhausen et al, 1967;Ipavich, F., 1997;Kallenbach et al, 1997;Kasper et al, 2015;Mason et al, 1998;Mukai et al, 1987;Oglivie & Wilkinson, 1969;Shearer et al, 2014;Von Steiger et al, 2001).The majority of these analyses are based on a combination of energy analysis by a spherical analyzer and time of flight (TOF) analysis using carbon foil as an incident marker. From a physical point of view, however, it is difficult to maintain an initial charge state through the measurement process (Bochsler et al, 2000).…”
Section: Introductionmentioning
confidence: 99%